Achaete-scute complex homologue-1 promotes development of laryngocarcinoma via facilitating the epithelial–mesenchymal transformation. Issue 6 (May 2017) - Ma, Huaci; Du, Xiaodong; Zhang, Shu; Wang, Qiang; Yin, Yong; Qiu, Xiaoxia; Da, Peng; Yue, Huijun; Wu, Hao; Xu, Fenglei
Laryngeal cancer is one of the most common fatal cancers among head and neck carcinomas, whose mechanism, however, remains unclear. The proneural basic-helix-loop-helix protein achaete-scute complex homologue-1, a member of the basic helix-loop-helix family, plays a very important role in many cancers. This study aims to explore the clinical value and mechanism of achaete-scute complex homologue-1 in laryngeal cancer. Methods including Cell Counting Kit-8, flow cytometry, Transwell invasion assays, and scratch assay were adopted to further explore the bio-function of achaete-scute complex homologue-1, whose expression was examined in fresh and paraffin chip of laryngeal carcinoma tissues by means of western blot and immunohistochemistry, after the interference of achaete-scute complex homologue-1; achaete-scute complex homologue-1, an overexpression in laryngeal carcinoma whose carcinogenicity potential was confirmed via western blot, was correlative with T classification (p = 0.002), histological differentiation (p = 0.000), lymph node metastasis (p = 0.000), and poor survival (p = 0.000). Multivariate analysis shows that achaete-scute complex homologue-1 overexpression is an independent prognostic factor unfavorable to laryngeal carcinoma patients (p = 0.000). Moreover, knocking down achaete-scute complex homologue-1 expression could significantly suppress the proliferation, migration, and invasion of laryngeal carcinoma cell in vitro and disorder epithelial–mesenchymal transformation–associated protein expression. Achaete-scute complex homologue-1 plays an important role in the genesis and progression of laryngeal carcinoma and may act as a potential biomarker for therapeutic target and prognostic prediction.